HUBUNGAN EFFORT REWARD IMBALANCE DENGAN KINERJA SDM DI RSU THALIA IRHAM TAHUN 2026 - Ardianti; Mohammad Ardani Samad (Journal of Hospital Administration and Management (JHAM), 2026)
Human resource (HR) performance is a crucial factor in determining the quality of hospital services. However, excessive work demands that are not balanced by adequate rewards may reduce employee motivation and productivity. One psychosocial factor that can influence employee performance is Effort-Reward Imbalance (ERI), a condition in which the efforts expended by workers are not proportional to the rewards they receive. This study aimed to analyze the relationship between Effort-Reward Imbalance and HR performance at Thalia Irham General Hospital in 2026. A quantitative study with a cross-sectional design was employed. The sample consisted of 120 healthcare and supporting staff selected through proportionate stratified random sampling. Data were collected using the ERI questionnaire and a validated and reliable HR performance assessment instrument. Data analysis was conducted using the Chi-square test with a 95% confidence level. The results showed that most respondents experienced high ERI levels (58.3%) and demonstrated moderate to low performance (61.7%). Bivariate analysis revealed a statistically significant relationship between Effort-Reward Imbalance and HR performance (p = 0.001). Employees experiencing high ERI were more likely to exhibit suboptimal performance compared to those with lower ERI levels. In conclusion, there is a significant relationship between Effort-Reward Imbalance and HR performance at Thalia Irham General Hospital in 2026. Therefore, improving reward systems, work recognition, and workload balance is necessary to enhance employee performance and organizational effectiveness.